Unlocking unallocated cloud capacity for long, uninterruptible workloads - Agarwal, Anup; Noghabi, Shadi; Goiri, Íñigo; Seshan, Srinivasan; Badam, Anirudh (NSDI, 2023)
Cloud providers auction off unallocated resources at a low cost to avoid keeping hardware idle. One such mechanism is Harvest VMs (HVMs). These VMs grow and shrink as the unallocated resources in a server change. While HVMs are larger in size and less prone to eviction compared to other low-cost VMs, their resource variations severely slow down long-running, uninterruptible (hard to checkpoint/migrate) workloads. We characterize HVMs from a major cloud provider and discover large spatial variations in their stability and resources. We leverage this diversity by predicting which HVMs will be stable enough to run tasks without preemptions. We use the predictions to inform scheduling and resource acquisition decisions. Our evaluation with real workloads shows that we can reduce mean and tail (90th percentile) job completion times by 27% and 44% respectively, at 75% lower cost than regular VMs.